Pengaruh Kompetensi Pedagogik Dan Kemampuan Berkomunikasi Guru Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Ilmu Pengetahuan Sosial Di SMP Negeri 35 Medan - Silaban, Fiorentina; Siagian, Lasma; Siahaan, Mian (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to see the success of learning determined by the teacher's communication skills and pedagogical skills in managing the teaching and learning process, known as pedagogical competence. The benefits of this study are to see the extent to which the influence of pedagogical competence and teacher communication skills on student learning motivation in Social Sciences subjects at SMP Negeri 35 Medan. The number of samples in this study was 86 students. The method used in this study is a quantitative method, namely an approach based on the reality of positivism and is used to examine a particular population or sample with the aim of testing the established hypothesis. Data collection techniques were carried out by distributing questionnaires to all samples with uniform treatment. Based on the results of data analysis, it was found that there was a significant influence between pedagogical competence (X₁) and teacher communication skills (X₂) on student learning motivation (Y) of class VIII at SMP Negeri 35 Medan. The results of the t-test (partial) showed that the t_count value was 6.444 with a significance value of 0.000. Since t_count > t_table (6.444 > 0.67746) at a significance level of 5% (α = 0.05), and the significance value <0.05 (0.000 <0.05), it can be concluded that both independent variables partially have a significant effect on students' learning motivation. In addition, the results of the F test also show a significance value of 0.000, which means <0.05. This shows that simultaneously, pedagogical competence and teacher communication skills have a significant effect on students' learning motivation.